Bolivia : Fiscal Transparency Assessment. (IMF Staff Country Reports; Country Report ;, 2014)
This paper elaborates Bolivia's fiscal transparency assessment report. The purpose of this IMF report is to facilitate countries in analyzing the fiscal situation through the appropriate basic, good, and advanced practices to identify which areas might benefit from reforms. These reforms intend to improve the coverage, opportunity, and quality of the macrofiscal information. The IMF report suggests that the issues merited improvements are related to the nonpreparation of audited annual consolidated financial statements of the central government and the absence of estimates and reports on tax expenditure.